Factors of Domestic Violence against Pregnant Women Referring to the trauma centers in Mashhad - Sayyed Majid Sadrzadeh; Seyed Mohammad Mousavi; Behrang Rezvani Kakhki; Shaghayegh Rahmani; Kosar Deldar; Sara Hematiali (Mashhad University of Medical Sciences, 2020)
Introduction: Violence against women is a global phenomenon, and varies based on the political, social and cultural characteristics of each place and location. Domestic violence is the most common type of violence against women. This study was performed with aim to investigate physical domestic violence and its most common contributing factors. Methods: This case-control study was performed in 2016-2019 on 23 pregnant women referred to trauma emergency of Shahid Hasheminezhad and Emal Reza hospitals of Mashhad with complaint of trauma due to domestic violence and other 23 patients due to trauma of other factors. Data collection was done by researcher-made questionnaire including three sections (demographic characteristics, type of domestic violence, and contributing factors). Data were analyzed by SPSS software (version 16) and Chi-square, Fisher-exact, Student t, or Mann-Whitney tests. PResults: During the three year period of study, 23 pregnant women referred to the emergency department of two referral hospitals in Mashhad due to domestic violence. Regression analysis showed that the most common contributing factors of domestic violence were previous history of domestic violence, unemployment and economic problems, history of previous hospital admission due to domestic violence and drug abuse of spouse. 16 patients (34.6%) leaved the hospital against medical advice in domestic violence group and 30 patients (65.2%) patients hospitalized for further evaluation and treatment. Leaving the hospital against medical advice was significantly higher in domestic violence trauma patients (p=0.001). Conclusion: Among the most important causes of domestic violence in the present study were the positive history of domestic violence in the person or family, as well as unemployment and economic problems.